2010
DOI: 10.1111/j.1558-5646.2010.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and Advertisement Calling in the Cricket Teleogryllus Commodus: Laboratory and Field Experiments

Abstract: If sexually selected traits reveal a male's heterozygosity or condition to females, then such traits should exhibit declines with inbreeding. We tested this by examining the effect of inbreeding on advertisement calling in male crickets Teleogryllus commodus.We investigated the effect of one generation of full-sibling mating on calling effort and fine-scale call structure. Inbreeding reduced calling effort but had no effect on call structure. We then compared the attractiveness of inbred and outbred calls in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 88 publications
(159 reference statements)
2
41
1
Order By: Relevance
“…In contrast to vertebrates, experimental tests of the effect of inbreeding and heterozygosity on sexual signalling in insects are scarce. However, Drayton et al [17] found that inbreeding reduced the calling effort of the cricket, Teleogryllus commodus, affecting the mating success of inbred males negatively. Similarly, inbreeding in Drosophila montana decreased the frequency of courtship song frequency associated with male's courtship success [18].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to vertebrates, experimental tests of the effect of inbreeding and heterozygosity on sexual signalling in insects are scarce. However, Drayton et al [17] found that inbreeding reduced the calling effort of the cricket, Teleogryllus commodus, affecting the mating success of inbred males negatively. Similarly, inbreeding in Drosophila montana decreased the frequency of courtship song frequency associated with male's courtship success [18].…”
Section: Discussionmentioning
confidence: 99%
“…Males who call more are more attractive to females [36]. Finally, we have already shown that inbreeding between full siblings affects both immune function [49] and male calling [39], [40], [44]. Inbreeding might therefore decrease the reliability of male calling as a signal of immune function by, for example, disrupting the usual proximate mechanism that determines the appropriate allocation of resources to calling and immune function.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, dietary manipulation has shown that advertisement calling effort is affected by nutrition [37], [38]. Importantly, inbreeding reduces advertisement calling effort [39] and alters fine scale advertisement call structure [40], indicating that both call effort and call structure might signal male fitness (given that inbreeding lowers fitness). It is therefore possible that advertisement calls signal key fitness components such as disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, females of the cricket Teleogryllus commodus detect and reject inbred males based on the reduced acoustic signals that they produce compared with outbred males [16,17]. In other case studies, females detect the genetic quality [18 -21] or the heterozygosity level [22] of their potential mating partners through the assessment of their olfactory cues.…”
Section: Introductionmentioning
confidence: 99%